INTEGRATED DEVELOPMENT OF CHEMICAL TEACHING MATERIALS ON MATERIAL BASED THERMOCHEMICAL SOFT SKILLS FOR VOCATIONAL STUDENTS (Jurnal Pendidikan IPA Indonesia, 2015)
Business and industrial field need workers who have not only good academic achievement but also the ability of hard skills and soft skills.  In order to prepare students who have a good academic skills, hard skills, soft skills it has to be done in all subjects including chemistry expertise to integrate the competencies of Motorcycle Engineering.  The research design uses One Group Pretest Posttest Design imposed on students in class XI SMK 1 Kedung TSM. Validator assessment results indicate that teaching materials developed very feasible for use in learning chemistry.  The result show that the learning device by using the integrated chemistry materials can increase students understanding of the thermo chemistry material with the acquisition of N-gain is at 0.63 or in the medium category.  Group of high-achieving students have the score of N-gain of 0.65, while the medium-achieving students get 0.63 and low-achieving students get 0.61, all have medium category.  Percentage  of students who passes the mastery learning  if mastery learning (KKM) 75 or reach 87 %.  The percentage of students’ soft skills in at least good criteria is at 87.10 %.  Students gave positive responses  90.71 % towards the learning material that is developed.